Draft 7th Five Year Plan 1985-90 and Annual Plan 1985-86 Vol.I Jammu and Kashmir Government - Planning Commission (Planning Commission, 1985)
Against the approved outlay of Rs. 900.00 crores an expenditure, of 936.79 crores is anticipated, during the 6th plan. Actual expenditure during 1st three years of the plan is of the order of Rs.490.17 crores, estimated expenditure for 1983-84 of Rs. 19577 crores and anticipated expenditure for 1984-85 of. The order of Rs, 250.85 crores. Government have authorized additional expenditure in certain sectors primarily with a view to providing relief to those sections of the population which are affected by the drastic fall in the tourist traffic in the last two seasons. Many similar measures are in the pipeline, Therefore, a clear picture of anticipated expenditure for the current year will emerge in the coming months. In the meanwhile the expenditure has been assumed at' the level of approved outlay.
Government of Jammu and Kashmir
Government of Jammu and Kashmir
Keywords: District Planning in Jammu and Kashmir state; Abstract of Financial Allocations; Physical Targets an Achievements; Minimum Need Programme Physical; Centrally Sponsored Centrally; Employment- Financial; Likely Manpower Requirements; District Sector Allocations; features of the sectoral programmes; Forest Corporation and Welfare Preservation; Land Reforms; Area development